INVARIANT SUBMANIFOLD OF (3k,k)STRUCTURE MANIFOLD - Singh, Lakhan; Gautam, Shailendra Kumar (IJRDO -JOURNAL OF MATHEMATICS, 2016)
In this paper, we have studied various properties of a 3 , k k  structure manifold and its invariant submanifold, where k is positive integer. Under two different assumptions, the nature of induced structure  , has also been discussed.